Systematic review and meta-analysis of linear and undulating periodized resistance training programs on muscular strength - Harries, S. K.; Lubans, D. R.; Callister, R. (The Journal of Strength and Conditioning Research, 2015)
Periodization is known to improve training adaptations but the most effective periodization approach for muscular strength development for a wide variety of populations is yet to be determined. This systematic review and meta-analysis examined all studies directly comparing linear and undulating periodized resistance training programs to determine and compare their effects on muscular strength. A systematic search of the MEDLINE, SCOPUS, and SPORTDiscus databases revealed 17 studies satisfying the inclusion criteria. There were a total of 510 participants in the included studies. Sixteen studies reported significant increases in strength for both periodization approaches. Five studies reported significant differences in improvements between groups. The meta-analyses determined that there were no differences in the effectiveness of linear vs. undulating periodization on upper-body or lower-body strength. The short-term nature of studies and the previous training history of participants were identified as potential confounding factors in the interpretation of findings. The results suggest that novelty or training variety are important for stimulating further strength development. Few studies have examined the effect of periodization approaches in adolescent or athletic populations.